EFFICIENCYMEASUREMENT OF ZAKAT INSTITUTION PROGRAM: CASE STUDY DOMPET DHUAFA INDONESIA - Aam Slamet Rusydiana; Hasna Maliha; Salman Al-Parisi (IJIBE (International Journal of Islamic Business Ethics), 2016)
Although social based, Zakat Institutions (OPZ) need to uphold professionalism, transparency and accountabilityin its management. Most recently, Zakat Core Principles is known as the measurement of zakat fundmanagement. This study would try to measure the efficiency of DompetDhuafa’s program as Decision Making Unit (DMU) in the level of efficiencyusing Data Envelopment Analysis (DEA) method. And also the research would look at the possibility of potential improvement from inefficient DompetDhuafa’s programs,input-output contribution and the reference contribution of the DMU.The results show that there are 6 DMU that efficient (100%) and inefficient as much as 18 DMU. The most inefficient program is wakaf fund (2012). In general, the main factor inefficiency ofDompetDhuafa program from 2010 to 2013 due to the distribution fund of DompetDhuafa program such as zakat, wakaf, humanity etc to ashnaf which is still less optimal.The distribution fund also has to increase up to 75.38%, then it is able to resolve the problem of poverty.